Corneal stromal dystrophies: a clinical pathologic study - Abreu,Elvira Barbosa (2012)
INTRODUCTION: Corneal dystrophy is defined as bilateral and symmetric primary corneal disease, without previous associated ocular inflammation. Corneal dystrophies are classified according to the involved corneal layer in superficial, stromal, and posterior dystrophy. Incidence of each dystrophy varies according to the geographic region studied. PURPOSE: To evaluate the prevalence of stromal corneal dystrophies among corneal buttons specimens obtained by penetrating keratoplasty (PK) in an ocular pathology laboratory and to correlate the diagnosis with patient age and gender. METHODS: Corneal button cases of penetrating keratoplasty from January-1996 to May-2009 were retrieved from the archives of The Henry C. Witelson Ophthalmic Pathology Laboratory and Registry, Montreal, Canada. The cases with histopathological diagnosis of stromal corneal dystrophies were stained with special stains (Peroxid acid Schiff, Masson trichrome, Congo red analyzed under polarized light, and alcian blue) for classification and correlated with epidemiological information (age at time of PK and gender) from patients' file. RESULTS: 1,300 corneal buttons cases with clinical diagnose of corneal dystrophy were retrieved. Stromal corneal dystrophy was found in 40 (3.1%) cases. Lattice corneal dystrophy was the most prevalent with 26 cases (65%). Nineteen were female (73.07%) and the PK was performed at average age of 59.3 years old. Combined corneal dystrophy was found in 8 (20%) cases, 5 (62.5%) of them were female and the average age of the penetrating keratoplasty was 54.8 years old. Granular corneal dystrophy was represented by 5 (12.5%) cases, and 2 (40%) of them were female. Penetrating keratoplasty was performed at average age of 39.5 years old in granular corneal dystrophy cases. Macular corneal dystrophy was present in only 1 (2.5%) case, in a 36 years old female. CONCLUSION: Systematic histopathological approach and evaluation, including special stains in all stromal corneal dystrophies is critical to establish the correct diagnosis.